Road and Bridge Construction Technology and Quality Control Measures and Analysis - Zhang, Guangchong; Li, Huiguang (Journal of Theory and Practice of Management Science, 2023)
With the rapid development of China's social economy, urban construction has undergone qualitative changes, and road construction and bridge engineering construction have become increasingly perfect, playing an important role in urban development and construction. Municipal road construction projects cover a wide range, with urban bridge construction running through them, effectively improving environmental and traffic issues, but there are still many areas that need improvement. This article proposes corresponding solutions for monitoring the construction quality of municipal roads and bridges, as well as the problems that arise, based on the development status of the city and the actual situation.